Influence of Opportunities and Challenges on the Success of Young Entrepreneurs with Social Media Marketing Moderation Variables - Illahi. S, Wahyu Nusantara; Puteri, Hesi Eka (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study aims to analyze the influence of Opportunities and Challenges on the Success of Young Entrepreneurs and examine the moderating role of Social Media Marketing in this relationship, focusing on café and restaurant businesses in Limapuluh Kota Regency and Payakumbuh City. Methodology: The research employs SEM PLS analysis using the SmartPLS 3.0 tool. Primary data were collected from 61 millennial café and restaurant business owners via a Likert scale-based questionnaire distributed through Google Forms. Results: Opportunities (X1) and Challenges (X2) have a positive and significant effect on the Success of Young Entrepreneurs (Y). Social Media Marketing (Z) positively and significantly moderates the relationship between Opportunities (X1), Challenges (X2), and Young Entrepreneur Success (Y). Findings: Effective Social Media Marketing amplifies the impact of Opportunities and Challenges on the success of young entrepreneurs in the café and restaurant sector. Originality: This study provides fresh insights into the role of digital marketing strategies in enhancing entrepreneurial success in a competitive business environment. Novelty: It integrates Social Media Marketing as a key moderating factor in the entrepreneurial framework of young business owners. Conclusions: Utilizing social media marketing is crucial for young entrepreneurs to achieve sustainable growth and competitiveness. Type of Paper: Empirical research paper.